Digital Building Permit As a Complex Permitting Document - V. A. Mayboroda (Теоретическая и прикладная юриспруденция)
The article puts forward a proposal for the formation of a digital building permit as a complex permitting document, the formation and issuance of which will include compliance with the requirements for landscaping both at the start of construction and at its completion. The digitalization of urban planning regulation, on the one hand, and the digitalization of the construction area of regulation should be harmonized through the improvement of the structure of the urban planning plan of the land plot, the implementation of which for the location of the capital construction facility will include the implementation of measures for landscape reconstruction of the development area. A comprehensive permitting document in the sense under discussion covers the stages of capital construction immediately preceding capital construction and the stages of subsequent landscape transformation of the territory, which compensates for the anthropogenic load of the erected object. The totality of each of the load values in the further development of the considered regulation, combined into a single data set (big date), will make it possible to resolve the issue of the load of the entire settlement as a whole with all possible certainty, without using calculation methods, whose estimates are of a probabilistic nature.